Comparison of efficiency between VNS and ANT-DBS therapy in drug-resistant epilepsy: A one year follow up study. (August 2021) - Zhu, Jin; Wang, Xueyuan; Xu, Cuiping; Zhang, Xi; Qiao, Liang; Zhang, Xiaohua; Yan, Xiaoming; Ni, Duanyu; Yu, Tao; Zhang, Guojun; Li, Yongjie
Highlights: The VNS and ANT-DBS were valid options in the treatment for patients with DRE. The total seizure reduction of ANT-DBS was better than VNS in patients with different clinical characteristic. VNS was beneficial to patients with older age of onset, older age at operation and focal seizures. ANT-DBS was suitable for those with older age at operation, focal seizures, history of craniotomy, and longer duration of epilepsy. Abstract: Vagus nerve stimulation (VNS) and anterior thalamic deep brain stimulation (ANT-DBS) have both been used for treatments of drug-resistant epilepsy (DRE). However, there is no comparative study on the effectiveness of two methods from one single center. 17 patients with DRE who underwent VNS therapy and 18 patients who underwent DBS were enrolled. A retrospective study was performed starting from baseline before operation extending to 12 months after operation. The seizure types, duration of epilepsy, age at implantation, failed numbers of antiepileptic drugs (AEDs) before operation, history of craniotomy, stimulation parameters and response rate were described. The analysis of liner regression on the age of onset, duration of epilepsy, numbers of AEDs, and the seizure reduction at 12 months after operation was applied. The mean seizure reduction in patients with DBS at 3, 6, 9 and 12 months after the operation was 57.22%, 61.61%, 63.94% and 65.28%, and that in cases with VNS was 36.06%, 39.94%, 45.24% and 48.35%, respectively. At 1 year after the operation, the patients with older operation age, focal seizures and older age of onset responded better to VNS; and those older operation age, focal generalized seizures, history of craniotomy and longer duration of disease responded better to DBS. The efficiency of ANT-DBS was higher than that of VNS at each follow up time point. Patients can choose the appropriate treatment according to the individual clinical characteristics.